Cassava processing in subSaharan Africa: the implications for expanding cassava production - Nweke, F.I. (SAGE Publications, 1994)
Cassava makes an important contribution to improving food security and rural incomes in sub-Saharan Africa, as it is tolerant of drought and poor soil and its cultivation does not require much labour. However, the fresh roots are bulky and perishable and need to be processed before they can be marketed; processing also removes the cyanogens which make many varieties poisonous in their raw form. Cassava roots are turned into granules, flours, pastes and chips, with a wide range of flavour and appearances for different areas and markets. Many different processing techniques are used, some of which make intensive use of fuel wood while others require a plentiful water supply. These requirements, as well as the need for a good transport and marketing infrastructure, limit the expansion of cassava production in sub-Saharan Africa, but technical solutions are being found.